EFFECTIVE SCHOOL DISCIPLINE – THE PRECONDITION FOR SUCCESSFUL TEACHING - Klasnić, Irena; Đuranović, Marina; Maras, Nevenka (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Students and their behaviour at school has been the subject matter of many scientific texts. This article aims to present Croatian and international literature of the past 30 years on the subject of school discipline. School and classroom discipline, or lack thereof, is a problem that troubles many schools around the world. The article discusses the epistemological roots of the term discipline. Looking at discipline from a pedagogical point of view, it is not considered to mean unquestioned obedience, but a requirement for achieving a high quality learning and teaching process. As such, discipline does not represent the objective of the teaching process, but rather a means of ensuring optimal and encouraging circumstances, as well as harmonious cooperation between students and teachers. Working in such conditions is characterized by a high degree of commitment and motivation of all participants of the teaching process. The article presents possible causes of indiscipline, the importance of a teacher’s personality in achieving the desired discipline and possible strategies for classroom management. The authors present several suggestions that could help teachers practitioners in establishing and maintaining discipline.